Comparison of Transactional and Transformational Leadership Models in Scout Extracurriculars at SMA Negeri 1 Leuwidamar - Alsri Nurcahya; Ohib Muhibburrohman; Anis Zohriah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Leadership is a crucial aspect of organizational dynamics, affecting individual performance, motivation, and development within it. What will be studied in this literature is the comparison of transactional and transformational leadership on the scout extracurricular at 1 Leuwidamar State High School. Transactional leadership focuses on exchanges between leaders and members, with an emphasis on supervision, incentives, and sanctions, while transformational leadership emphasizes the development of shared vision, motivating through inspiration, intellectual stimulation, and individual attention. The aim of this literature is to find out the differences between these two models of leadership in the context of practical application, their impact on extracurricular performance, as well as their implications for managing change and creating a sustainable work culture in the scout extracurricular at 1 Leuwidamar State High School. The method used in this research is qualitative research with the Field Research approach. In this case, the author conducted field research on Scout Extracurricular at Leuwidamar State High School 1, which relates to the comparison of transactional and transformational leadership models. Thus, both models also have context and need within the organization to find an optimal balance between maintaining stability and stimulating change in leading an institution. The results of both models can provide valuable insights in developing effective and adaptive leadership strategies, as well as having a significant impact on State High School 1 Leuwidamar.